2007
DOI: 10.1007/s11038-007-9221-z
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia Mission: Expected Applications to Asteroid Science

Abstract: Earth Moon and Planets, 101, pp. 97-125, http://dx.doi.org./10.1007/s11038-007-9221-zInternational audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 34 publications
1
81
0
Order By: Relevance
“…As has been shown by Kaasalainen et al (2004Kaasalainen et al ( ) orĎurech et al (2005 and demonstrated on real targets byĎurech et al (2009), physical models of asteroids can also be derived from photometry that only sparsely samples brightness variations. This kind of photometric data will be provided by all-sky surveys like Pan-STARRS (Panoramic Survey Telescope and Rapid Response System), LSST (Large Synoptic Survey Telescope), or Gaia (Mignard et al 2007), and we expect an avalanche of new asteroid models in the next decade.…”
Section: Introductionmentioning
confidence: 99%
“…As has been shown by Kaasalainen et al (2004Kaasalainen et al ( ) orĎurech et al (2005 and demonstrated on real targets byĎurech et al (2009), physical models of asteroids can also be derived from photometry that only sparsely samples brightness variations. This kind of photometric data will be provided by all-sky surveys like Pan-STARRS (Panoramic Survey Telescope and Rapid Response System), LSST (Large Synoptic Survey Telescope), or Gaia (Mignard et al 2007), and we expect an avalanche of new asteroid models in the next decade.…”
Section: Introductionmentioning
confidence: 99%
“…But the data improvement will be considerable, both in terms of quantity (observations are expected for ∼300.000 asteroids, [29]) and quality (the photometric accuracy is estimated to be ∼0.01 mag for asteroids up to 18 magnitude, and ∼0.03 mag up to 20 magnitude [7], [8]). As a result of this enormous amount of new data, asteroid models for at least 10.000 objects are expected.…”
Section: Shape Modelsmentioning
confidence: 99%
“…The range of latitudes around zero for which the inversion is presenting a lower reliability is getting wider the smaller the number of measurements is. Still, the good news is that, on the average, main-belt asteroids will be detected on the Gaia focal plane for a number of times between 60 and 70 during the five-year operational lifetime of the mission (Mignard et al 2007). Therefore the number of problematic asteroids for which Gaia photometric inversion might produce wrong solutions will represent a small part (although still several hundreds) of the hundreds of thousands of asteroids observed.…”
Section: Influence Of the Number Of Measurementsmentioning
confidence: 99%